2018
DOI: 10.2478/alife-2018-0041
|View full text |Cite
|
Sign up to set email alerts
|

Valorification of Jerusalem Artichoke Tubers (Helianthus Tuberosus) for Achieving of Functional Ingredient with High Nutritional Value

Abstract: Jerusalem artichoke tubers (Helianthus tuberosus) are distinguished by their protein, minerals (potassium, calcium, magnesium, iron, etc.) and inulin content. Inulin can be used in the diet of diabetics as a substitute of sugar, without having an impact on blood glucose. At the same time, an international study had shown that due to their inulin content, regular consumption of Jerusalem artichoke tubers can help to prevent type 2 diabetes. In this paper are presented the results of the researches performed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…The processed samples showed a significant decrease at p<0.05 level when compared with unprocessed-JATF samples. The present data is comparable with 22 who reported that white variety of Jerusalem artichoke tuber had 300.12 ± 30.01 mg/100 g potassium content. Likewise, the potassium content of boiled sweet potato (3,061.08 mg/100 g) was significantly reduced when compared with unprocessed (3,288.24 mg/100 g) 29 .…”
Section: Resultssupporting
confidence: 91%
“…The processed samples showed a significant decrease at p<0.05 level when compared with unprocessed-JATF samples. The present data is comparable with 22 who reported that white variety of Jerusalem artichoke tuber had 300.12 ± 30.01 mg/100 g potassium content. Likewise, the potassium content of boiled sweet potato (3,061.08 mg/100 g) was significantly reduced when compared with unprocessed (3,288.24 mg/100 g) 29 .…”
Section: Resultssupporting
confidence: 91%
“…Waldspindel. Considerable differences in the antioxidant capacity of different Jerusalem artichoke cultivars were also reported by Catana et al [42]. The antioxidant capacity of cvs.…”
Section: Antioxidant Capacitymentioning
confidence: 53%
“…Inulin content in Helianthus tuberosus ranges from 14-25% of fresh tuber mass (36,(38)(39)(40). Inulin is a fructan and a valuable prebiotic reducing the development of pathogenic bacteria in the intestines and facilitating the functioning of bifidobacteria capable of enzymatic hydrolysis of the β-1,2-glycosidic linkage (16,36). Inulin molecules are varied, like starch, and can contain more or less fructose.…”
Section: Chemical Composition Of Tubers and Aerial Partsmentioning
confidence: 99%
“…<200) and changes depending on cultivars, weather conditions and the physiological and chronological age of the plant. The degree of polymerization of inulin obtained from Helianthus tuberosus tubers can be equal to inulin extracted from chicory roots or even higher (16,36). A lot of research was conducted on refined prebiotics, such as inulin or fructo-oligosaccharides (FOS) as nutraceuticals, but there is very little information on the prebiotic potential of products rich in inulin and FOS, such as Helianthus tuberosus L. Samal et al (12) conducted a research in order to assess the prebiotic activity of Helianthus tuberosus tubers on rats.…”
Section: Chemical Composition Of Tubers and Aerial Partsmentioning
confidence: 99%
See 1 more Smart Citation